2014
DOI: 10.4271/2014-01-2670
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of the Effect of Piston Shapes and Fuel Injection Strategies on In-Cylinder Conditions in a PFI/GDI Gasoline Engine

Abstract: INTRODUCTIONControlled Auto-ignition (CAI) combustion has been shown to effectively reduce the NOx emissions and increase fuel efficiency [1] and it has been subject to extensive studies in the past few decades. However, the lack of direct control on the auto-ignition process and relatively narrow operation range inhibit the practical application of this low temperature high efficient combustion mode [2]. In order to enhance the control of auto-ignition and extend the operation range of CAI combustion, spark i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Three piston bowl designs, as shown in Fig. 3, were designed from the origin Flat Piston (FP) in order to achieve the stratified mixture [37]. Compared to Piston A (PA), Piston B (PB) has a larger bowl diameter.…”
Section: Simulations Setup and Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Three piston bowl designs, as shown in Fig. 3, were designed from the origin Flat Piston (FP) in order to achieve the stratified mixture [37]. Compared to Piston A (PA), Piston B (PB) has a larger bowl diameter.…”
Section: Simulations Setup and Validationmentioning
confidence: 99%
“…In addition to the piston shapes, both the start of injection timing [20,[34][35][36] and the direct injection ratio [20,26,31] play important roles on controlling in-cylinder fuel stratification patterns and combustion process. Our previous study revealed the effect of piston shapes, start of injection (SOI) timings and direct injection ratios on the in-cylinder conditions, including in-cylinder flow conditions, fuel stratification patterns and thermal conditions [37].…”
Section: Introductionmentioning
confidence: 99%
“…Dam and Rutland [16] predicted the gasoline sprays from a multi-hole injector at various background temperatures (400-900 K) and densities (3-9 kg/m3) with the standard KHRT breakup model and found that it was necessary to adjust breakup model parameters, including the break-up length, as functions of the density ratio in order to accurately simulate the large-scale vapor mixing. Wang et al [17][18][19] and Bonatesta et al [20] calibrated the RD model to predict the gasoline spray and combustion process in wall-guided DI gasoline engines with the multi-hole injector. Sim et al [21] modeled the gasoline spray from an outward-opening piezoelectric injector with the modified KHRT breakup model, and the initial Sauter mean diameter (SMD) values were varied in order to validate against the measurements under different background conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve optimal combustion during the spark ignition operation in the BUSDIG engine, the fuel injection and local fuel-air equivalence ratio (ER) around the spark plug should be controlled to near stoichiometry for stable ignition and faster flame propagation. [10][11][12][13] It has been shown that the fuel stratification can be achieved by a suitable bowl piston shape 14,15 and organized in-cylinder flow motions 16,17 in combination with an appropriate DI strategy. Both the start of injection (SOI) timing [18][19][20][21] and the split DI ratio 10,19,22 play important roles on controlling in-cylinder fuel stratification patterns and the subsequent combustion process.…”
Section: Introductionmentioning
confidence: 99%